SYNTHESIS OF MESOPOROUS TITANIA BY POTATO STARCH TEMPLATED SOL-GEL REACTIONS AND ITS CHARACTERIZATION - Canggih Setya Budi; Indriana Kartini; Bambang Rusdiarso (Universitas Gadjah Mada, 2010)
Mesoporous titania powders with high-order crystalline building blocks had been synthesized through the sol-gel process using potato starch gel template. Internal spongelike pore structure of starch gel template was generated by heating the starch granules at 95 °C in water solution and freezing the starch gel at -15 °C. The synthesis routes were performed by immersing the starch gel template for 4 days into the white colloidal solution of TiO2 nanoparticles, which were prepared by hydrolyzing titanium (IV) tetraisopropoxide (TTIP) in ethanol at pH 1. Mesoporous TiO2 powders were obtained by two different ways of template removal, performed by calcination of the TiO2-starch composites at 600 °C for 4 h or combination of extraction with ethanol-HCl (2:1) at 80 °C and calcination at 500 °C for 4 h. Fourier Transform Infra Red (FT-IR) spectra shows both of template removal methods result in decreasing of characteristic vibrational band of the starch hydrocarbon on the resulted TiO2 powders. The X-Ray Diffraction (XRD) pattern imply that the concentrations of starch gel template influence the anatase crystallite peaks intensity of the synthesized TiO2 powders. TiO2 templated by 20% of starch sponges gel has highest intensity of anatase crystallite. Scherrer calculation inidicated that anatase particle size has nanoscale dimmension up to 12.96 nm. The nano-architecture feature of mesoporous TiO2 scaffolds was also evaluated by the Scanning Electron Microscope (SEM). It is shown that mesoporous TiO2 framework consist of nanocrystalline TiO2 particles as buiding blocks. The N2 adsorption-desorption isotherm curves assign that TiO2 powder resulted from extraction-calcination route has higher mesoporosity than that of only calcinated. The synthesized mesoporous TiO2 powder exhibits high Brunauer-Emmet-Teller (BET) specific surface area up to 65.65 m2/g.